Risk Preferences of Doctors, Lawyers and Businessmen/women: An empirical analysis - Atnas, Stephanie (2010)
The aim of this dissertation is to investigate the differences in risk preferences of doctors, lawyers and businessmen/women. Using an experimental approach, 108 questionnaires were collected from doctors, lawyers and businessmen/women in Cyprus. After reviewing the limited literature on risk preferences in occupation, the main findings indicate that there are differences in risk preferences amongst these three professions. Specifically doctors are more risk averse than lawyers and businessmen. Also, this research finds no evidence of gender and age significant differences in risk preferences amongst professionals.